Implementasi Tri Hita Karana Sebagai Dasar PelaksanaanHukum Lingkungan Pada Desa Penglipuran, Bali - Emy Handayani emy (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
This writing aims to determine the application of Tri Hata Karanacustomary regulations as the basis for implementing Environmental Lawin Penglipuran Village, Bangli Regency, Bali Province. The researchmethod used is Juridical Empirical. The approach method used is theobservation of existing customary regulations combined with statutoryregulations. Tri Hita Karana is a reflection or reflection of the values ofPancasila in a culture or teachings in Indonesian society which includeatashyangan (harmonious relations that take place between humans andGod), pawongan (harmonious relations between humans and fellowhuman beings), and paleahan (harmonious relations between humans andGod). between humans and nature). The awig-awig are written andunwritten rules made by villagers (krama desa) with the aim of regulatingthe order of their daily life. It is local wisdom which is a strong foundationin good management of natural resources and the environment. Awigawig of Penglipuran village regulates things like house layout, felling oftrees as a form of environmental preservation, waste management, andother programs. These regulations are adhered to in order to preserve theancestral heritage as well as contain magical values which are stillbelieved by the villagers.